Analysis of Total Suspended Solid Algorithm on Tuban Coast with 2 Channel Approach of Visible Light Wavelength Satellite Image - Hendrata Wibisana,; Bagas Aryaseta,; Primasari Cahya Wardhani, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Satellite image channels have been widely used by researchers from various countries to map and analyze variables that have a lot of influence on ecosystem changes including the total suspended solid levels scattered on the coast. The use of 1 channel in satellite images provides many results with various good correlations, but in this study, we want to try to use a 2-channel approach to get more optimal results from total suspended solid mapping. The area of interest for research is the Tuban coastline which has a fairly flat and not hilly coastal morphology so that sea currents that carry solids have characteristics in their growth over time. The method used to construct the algorithm of these 2 channels is the use of reflectance values of visible light wavelengths in blue, green and red channels. The results obtained from the calculation of the 2-channel algorithm show a fairly good suitability and correlation, especially in the comparison of the blue channel with the red channel with an R2 value of 0.76 so that it can be used as a reference to monitor total suspended solids as well as a comparison for the calculation of 1 channel. The conclusion obtained is that the channels from satellite images have their own characteristics in providing reflectance values for objects on earth so that with the right combination of channels will be able to obtain accurate results in mapping total suspended solids.